Morphological and molecular characterization of fungus isolated from tropical bed bugs in Northern Peninsular Malaysia, Cimex hemipterus (Hemiptera: Cimicidae) - Abdul Hafiz, Ab Majid; Abd Hafis, Abd Rahim; Zulaikha, Zahran; Nor Azliza, Ismail; Wardah, Abdul Rahman; Kartiekasari Syahidda, Mohammad Zubairi; Hamady, Dieng; Tomomitsu, Satho (Elsevier, 2015)
Objective: To investigate some morphological and molecular characteristics of fungal parasites isolated from wild tropical bed bug, Cimex hemipterus. Methods: A series of culture methods were used to obtain fungal isolates from field-collected bed bugs. Characteristics of the isolates such as colony appearance, mycelial texture and pigmen-tation were studied to explore their morphology. Isolates were also subjected to a PCRbased genotyping test. Results: There were noticeable differences in morphological characteristics among the four isolates. Conidial areas of one isolate were dark green, whereas those of the remaining colonies were olive-green, black or dark brown. Conidia of the dark green isolate were globose, while those of olive-green, black and dark brown isolates were globose to subglobose, globose to spherical and globose to subglobose/finely roughened, respectively. These morphological specificities and the molecular analyses showed that the fungal internal transcribed spacer ribosomal region and β-tubulin gene sequences of the isolates shared clade with Trichoderma and Aspergillus sequences. Conclusions: Overall, the new discovery of common pathogens in agricultural field developed in live bed bugs storage tank may initiate the use of biological agents in later years.